2014
DOI: 10.4028/www.scientific.net/amr.910.246
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Technique and Mechanical Property Evaluations of Polypropylene/Short Coir/Short Glass Fiber Wood Plastic Composites

Abstract: This study uses a single screw extruder to make short coir (SC), an agricultural waste, high-strength short glass fiber (SGF), and polypropylene (PP) into pellets, which are then made into wood plastic composites (WPC) on an injection machine. During the process, maleic anhydride grafted polypropylene (PP-g-MA) is used as a coupling agent to improve the interfacial adhesion between coir and PP as well as between SGF and PP. A tensile strength test, flexural strength test, and Izod impact strength test are perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was reported that coextruded WPCs filled with silane-treated precipitated CaCO3 and wood fiber in the shells had reduced water absorption and thermal expansion values (Kim et al 2013). Despite their advantages, WPCs have poor interfacial compatibility between the wood fiber and polymer matrix (Zhang et al 2004;Lin et al 2014;Ou et al 2014). However, the use of fillers has made it difficult to obtain good dispersion and strong interfacial adhesion, which can affect the interfacial compatibility between the core and shell layer of structured WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that coextruded WPCs filled with silane-treated precipitated CaCO3 and wood fiber in the shells had reduced water absorption and thermal expansion values (Kim et al 2013). Despite their advantages, WPCs have poor interfacial compatibility between the wood fiber and polymer matrix (Zhang et al 2004;Lin et al 2014;Ou et al 2014). However, the use of fillers has made it difficult to obtain good dispersion and strong interfacial adhesion, which can affect the interfacial compatibility between the core and shell layer of structured WPCs.…”
Section: Introductionmentioning
confidence: 99%